Graph Theory to Map Nursing Knowledge of Diagnosis and Interventions in Women's Health - Jensen, Rodrigo; Alegre, Patrícia Helena Corrêa [UNESP]; Venâncio, Jéssica Aparecida Luciano [UNESP]; Gomes Junior, Luiz Celso; Duarte, Marli Teresinha Cassamassimo [UNESP]; Peres, Heloisa Helena Ciqueto (IOS Press, 2024)
Objective: Apply Graph Theory to analyze and map knowledge about nursing diagnoses and interventions, based on records of consultations carried out by nurses, in women's health, in primary health care. Methods: Secondary data from a cross-sectional study were used. Records of nursing consultations carried out during the month of October 2016, in 21 health units, in a Brazilian municipality were analyzed. Network analysis was carried out using Graphs from 61 nursing consultations. Results: 175 diagnoses were recorded, an average of three per consultation; and 380 interventions, an average of six per consultation. In the analysis, four diagnostic and four intervention network groupings were identified. Conclusions: The mapping allowed reflection on phenomena of interest to Nursing and fostering critical thinking in decision making. The findings are useful for teaching and training nurses, as well as strengthening the use of standardized language systems.
Keywords: Graph Theory; Nursing Process; Primary Health Care; Standardized Nursing Terminology; Women's Health